1995
DOI: 10.1128/jvi.69.11.7244-7247.1995
|View full text |Cite
|
Sign up to set email alerts
|

Avian homologs of the mammalian low-density lipoprotein receptor family bind minor receptor group human rhinovirus

Abstract: Avian oocyte-specific very low density lipoprotein receptor specifically binds human rhinovirus of the minor receptor group on ligand blots and in solution. The solubilized receptor protects cells against infection in a dose-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 24 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…We have previously shown that detergent-solubilized OVR, the avian homologue of mammalian VLDLR, inhibits infection of HeLa cells by HRV2 (9). However, since this receptor is not involved in viral infection (rhinoviruses do not replicate in any species except humans and other primates), it was of interest whether soluble LDLR fragments would also inhibit infection.…”
Section: Soluble Ldlr Fragments Inhibit Minor Group Hrv Infectionmentioning
confidence: 99%
“…We have previously shown that detergent-solubilized OVR, the avian homologue of mammalian VLDLR, inhibits infection of HeLa cells by HRV2 (9). However, since this receptor is not involved in viral infection (rhinoviruses do not replicate in any species except humans and other primates), it was of interest whether soluble LDLR fragments would also inhibit infection.…”
Section: Soluble Ldlr Fragments Inhibit Minor Group Hrv Infectionmentioning
confidence: 99%
“…Soluble recombinant human VLDLR inhibits HRV infection. We have previously shown that the chicken ovarian VLDL receptor (OVR) binds HRV2 on ligand blots and inhibits HRV2 infection of HeLa cells in its detergent solubilized form (8). However, HRVs fail to replicate in birds; therefore, the function of OVR as a viral receptor is questionable.…”
Section: The Protein Shed From Hela Cells Is a Fragment Of Vldlrmentioning
confidence: 99%
“…The various members of the large family Picornaviridae use a number of different membrane receptors to attach to and ultimately infect their target cells. These surface proteins belong to families as diverse as the immunoglobulin (Ig) superfamily (14,45,47), integrins (4,5), complement-inactivating proteins (24,49), lipoprotein receptors (17,20), and mucintype glycoproteins (23). For several representative picornaviruses, data have been presented which strongly suggest that the virions are internalized by their respective receptors into endosomes (50), where it was shown for foot-and-mouth disease virus and for the minor-group rhinovirus human rhinovirus type 2 (HRV2) that the low intravesicular pH triggers RNA release (3,39).…”
mentioning
confidence: 99%